The Reliability and Usability of District Health Information Software: case studies from Tanzania - Lungo, Juma H. (My University, 2008)
The District Health Information System (DHIS) software from the Health Information System Programme (HISP) based in South Africa is widely implemented in many developing countries as a health data analysis tool. Through the HISP Tanzania project, the DHIS was piloted in five districts in Tanzania. The objective of this study was to qualify and quantify the extent to which district health workers consider the adaptation of the DHIS software to the needs of the routine health management information system. In a period of 14 months (from June 2003 to August 2004) data were collected from health workers trained to use the software through a triangulation of various qualitative data collection techniques including interview, questionnaire, participant observations and retrospective testing. The software was evaluated in terms of reliability, usability and user satisfaction. In general the reliability of the software was rated high but its usability was rated to be low. The software was found not to accommodate some health data from various health programmes and there was a mismatch between the implemented online data entry forms/reports and their respective paper-based forms/reports. The study recommends improved design of the DHIS user interface (forms) and reports to replicate the paper-based forms in order to assure usability and reduce the incidences and impact of human errors in the keying-in of health data.
Keywords: district; health information; software; reliability; usability; Tanzania